Sierra Leone : : Diamond prospecting by the Consolidated African Selection Trust Ltd ; 2 - Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1933)
Colonial Office memoranda concerning diamond mining in Sierra Leone, the agreement between the government and the Consolidated African Selection Trust on the formation of the Sierra Leone Selection Trust and transfer of mining rights, and tax concessions for the new company